SINTESIS KATALIS KARBON AKTIF CANGKANG BIJI KARET DIIMPREGNASI CaO DAN KOH UNTUK PEMBUATAN BIODIESEL DARI MINYAK JELANTAH - Raka Ade Dwi Cahaya; Fadarina HC; Mustain Zamhari (Politeknik Negeri Sriwijaya, 2022)
The use of catalysts is very influential in the production of biodiesel because it can accelerate the production of biodiesel. The catalysts that are often used to make biodiesel are homogeneous base catalysts such as NaOH and KOH. The use of alkaline catalysts is faster than acid catalysts, so alkaline catalysts are more often used. Homogeneous catalysts have the disadvantage that they are difficult to separate. Disadvantages are overcome by using heterogeneous catalysts. The problem encountered when using heterogeneous catalysts is the diffusion process, so the heterogeneous catalyst must have a large surface area. The material with a large surface area that has the potential to be part of the catalyst is activated carbon from rubber seed shell. Activated carbon cannot directly used as a catalyst in the production of biodiesel because it does not have an active site, so activated carbon needs to be prepared by impregnation of the active site onto the surface of activated carbon such as CaO and KOH. This research varying the mixture ratio when impregnation between activated carbon CaO and KOH and then tested on the production of biodiesel for check the activity and selectivity of catalyst. The best CaO:AC ratio in the synthesis of CaO/KOH/AC catalysts is (2.5 : 7.5) with the best KOH concentration of 25% which produces a yield of 96.4%. The biodiesel produced using a CaO/KOH/AC catalyst has met several parameters of SNI 7182:2015, where the catalyst with the best yield produces a density of 0.866 gr/ml, a viscosity of 4.00 cSt, a flash point of 162.6 and a cetane number of 75.5.